2020
DOI: 10.3390/healthcare9010015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Low Testosterone According to Health Behavior in Older Adults Men

Abstract: Testosterone is a representative sex hormone for men, and low testosterone causes erectile dysfunction and cardiovascular disease. The purpose of this study was to investigate the association between low testosterone (LTT) and health behaviors, such as alcohol, smoking, and exercise habits. We included 2980 men aged 65 to 80. Total serum testosterone and body composition were measured. A testosterone level less than 300 ng/dL was defined as low testosterone. A questionnaire on smoking, alcohol, and exercise wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
(13 reference statements)
1
10
0
Order By: Relevance
“…He found that testosterone increased immediately after medium-intensity training but began to decrease when the exercise time was more than 2 h [ 34 ]. A possible reason for this is that short-term inexhaustible exercise can promote the secretion of testosterone [ 35 ]. Slivka et al [ 36 ] found that testosterone concentrations decreased continuously among athletes during 21 days of mountain bike cross-country training.…”
Section: Discussionmentioning
confidence: 99%
“…He found that testosterone increased immediately after medium-intensity training but began to decrease when the exercise time was more than 2 h [ 34 ]. A possible reason for this is that short-term inexhaustible exercise can promote the secretion of testosterone [ 35 ]. Slivka et al [ 36 ] found that testosterone concentrations decreased continuously among athletes during 21 days of mountain bike cross-country training.…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed in respect to nicotine's effect on testosterone because it has been found that those who smoke more have increased risks of low testosterone levels. 18 The results from Table 3 demonstrate that all these drugs of abuse may alter testosterone levels, even if they do not always necessarily lower them. [67][68][69][70][71][72][73][74] Further exploring the drugs of abuse that have an effect on lowering testosterone levels is essential to exploring the proposed hypothesis.…”
Section: Effects Of Drug Abuse On Testosterone Levelsmentioning
confidence: 93%
“…One study examining both aerobic exercise and anaerobic exercise found that both had an intensity-dependent increase in testosterone levels, thus decreasing the risk these males had of developing low testosterone levels as they age. 18 Aging also has a direct effect on testosterone levels in females. 19 As females age and undergo menopause, their testosterone levels decline drastically to 15% their premenopausal levels.…”
Section: Effects Of Aging and Obesity On Testosterone Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at the degree of glycemic control, we noticed that serum testosterone levels were majorly impacted by and negatively correlated to poor glycemic control, which is defined as HbA1c ≥7%. [9] Furthermore, this negative correlation explains why it was found that, even though, diabetic patients generally have lower serum testosterone levels than the general population, those with tight glycemic control (HbA1c of 6.5-6.9%) had serum testosterone levels closer to the general population in spite of having DM (Figure 2).…”
Section: Glycemic Controlmentioning
confidence: 98%